PEMANFAATAN KELAS IBU HAMIL OLEH IBU HAMIL DALAM PENCEGAHAN KOMPLIKASI KEHAMILAN DI WILAYAH KERJA UPT PUSKESMAS GUNTUNG - Rayani, Gusti Nur; Suhartati, Susanti; Budi, Setia (Midwifery And Complementary Care, 2024)
Background: Efforts to reduce maternal and child mortality cannot be separated from the role of community empowerment, one of which is carried out through the holding of Pregnant Women Classes and the Birth Planning and Complication Prevention Program. The data in the working area of ​​the Guntung Health Center contained 23 pregnant women who experienced obstetric complications. Pregnant Women Class activities aim to increase the knowledge and skills of mothers and families about pregnancy. Objective: To find out the utilization of pregnant women's classes by pregnant women in an effort to prevent pregnancy complications in the working area of ​​the Guntung Health Center. Methods: This type of quantitative research descriptive observational design. The sample consisted of 34 pregnant women in the working area of the Guntung Health Center in February 2023, using an accidental sampling technique. Retrieval of data using a questionnaire sheet. Data were analyzed using univariate analysis. Result: Respondents aged 20-35 years 79.4%, parity of multipara respondents 44.1%, respondents who were high school graduates 38.2% and housewife respondents 73.5%. Class utilization of pregnant women who use well is 58.8%, quite good is 11.8% and is not good is 29.4%. Conclusion: Utilization of classes for pregnant women put to good use. It is hoped that the Puskesmas will always provide optimal health services so that the implementation of the Pregnant Women's Class program is carried out routinely as a preventive effort and early detection of complications of pregnancy, childbirth, postpartum and babies.